DIGITAL REORIENTATION OF ISLAMIC HIGHER EDUCATION IN INDONESIA - Kastolani Kastolani (Akademika : Jurnal Pemikiran Islam, 2019)
The digital era and rapid technological developments require responses from various institutions to be able to survive and be able to use it well. Islamic education also needs to respond to this. Therefore, the reorientation of Islamic education in the digital era is important to discuss. This article aims to discuss various thoughts related to the reorientation of Islamic education in the digital era. The discussion is focused on approaches, models, and methods in Islamic studies at Islamic higher education using descriptive analysis. This article recommends the reorientation of Islamic education in the digital era can be done through three things, namely first, with a historical approach, second, by avoiding pseudo-diversification models, and third, by using Blended e-learning methods. Thus the Islamic Higher Education institutions can carry out its role and function in education that is sensitive to the times and at the same time the manifestation of Islam as rahmatanlil 'alamin in the digital era. Keywords: Blended E-Learning, Digital Era, and Technology.